Web-Based Data Collection Service System Design for the Social Services Department of Nias Selatan - Laia, Finis Hermanto; Laia, Firdaus; Syahidi, Aulia Akhrian; Buulolo, Progresif (LPPM Universitas Nias Raya, 2025)
The Social Services Department of Nias Selatan faced challenges in managing data on Penyandang Masalah Kesejahteraan Sosial (PMKS) due to manual processes and geographical constraints across the district. This study aimed to design a web-based data collection service system to improve data management, complaint handling, announcements, and dissemination of social welfare information. Data were collected through observations and interviews, and the system was modeled using Unified Modeling Language (UML) diagrams, including Use Case, Activity, Sequence, and Class Diagrams. The system was developed using the waterfall method, with PHP and MySQL as the programming and database technologies. Functional testing using the black box method showed that the system functioned as expected. The resulting web application facilitated effective and transparent management of PMKS data, enhanced complaint services, and improved information delivery to the community. The system supported the Social Services Department in performing its duties more efficiently, particularly in managing PMKS data across multiple sub-districts. Future developments were considered, including security enhancements and integration with social media platforms for broader information dissemination.